Study of impact of screen time in early adolescent school children - Hapani, Nitya T.; Hapani, Tejas P. (International Journal of Contemporary Pediatrics, 2025)
Background: Excessive screen time exposure is a widespread issue among modern school children. Indian data on risk factors and the adverse consequences of screen use in healthy, school-going children is limited. This study aimed to explore types of screen exposure and evaluate associations between screen time and variables including sleep quality, academic performance, family structure, behavioural and medical problems, and outdoor activity. Methods: This was a cross-sectional observational study conducted from 1 February 2025 to 31 March 2025 at The Galaxy School, Rajkot, Gujarat. Parents of grade 4 and 5 students were surveyed using structured questionnaires. BMI was assessed according to Indian academy of pediatrics (IAP) charts. Data was analysed using SPSS version 26. Results: A total of 155 students (54% male) participated. The mean screen time was 3 hr 35 min (range: 40 min-8 hr 30 min). Nuclear family structure and both parents working was associated with higher screen time (4 hr 19 min and 4 hr 18 min respectively). Dry eye (27%), stubbornness (45%), and headaches (10%) were frequent complaints. Neck/shoulder pain, insomnia, and night terrors were associated with notably higher-than-average screen exposure. Academic performance was inversely related to screen time. Conclusions: Screen exposure was reported to be universal. Risk factors for excessive screen time include nuclear family settings and dual working parents. Behavioural, sleep, and physical health indicators demonstrate measurable associations with screen use, underscoring the need for early interventions.